2020
DOI: 10.1002/smtd.202000507
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Graphene Derivatives in Perovskite Solar Cells

Abstract: traditional power generation methods such as coal and natural gas due to the low-cost raw materials and relatively simple structures of PSCs. [14,15] Both the high efficiency and low cost make PSCs a promising candidate to realize commercialization. Currently, to further improve the performance of PSCs and accelerate the commercialization progress, there are still several challenges to be overcome. For example, the ion migration caused by weak Coulomb force in perovskite lattice is considered to be detrimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…The chemical components of metal halide perovskite are bonded through weak interactions such as ionic interaction, hydrogen bonding, and van der Waals forces, which results in the soft-material nature of perovskite semiconductors. Irreversible decomposition of organic species and the ion migration occur easily in PSCs under moisture penetration, continuous light soaking, thermal stress, and external electric field [11,[40][41][42], which cause damage to both the perovskite and charge transport layers. On the other hand, the leakage of Pb during long-term operation of PSCs under bad weather conditions could further cause environmental and public health risk, which should also be considered as an important stability issue to be addressed for future commercialization.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical components of metal halide perovskite are bonded through weak interactions such as ionic interaction, hydrogen bonding, and van der Waals forces, which results in the soft-material nature of perovskite semiconductors. Irreversible decomposition of organic species and the ion migration occur easily in PSCs under moisture penetration, continuous light soaking, thermal stress, and external electric field [11,[40][41][42], which cause damage to both the perovskite and charge transport layers. On the other hand, the leakage of Pb during long-term operation of PSCs under bad weather conditions could further cause environmental and public health risk, which should also be considered as an important stability issue to be addressed for future commercialization.…”
Section: Stabilitymentioning
confidence: 99%
“…Besides the efficiency progress, the long-term stability of PSCs against damp, light, and heat also improved significantly in recent years, which could be attributed to the construction of diffusion barrier against ion migration, additive engineering, design of chemically inert carbon-based electrodes, and development of cell encapsulation technique to reduce the lead leakage from a broken PSC module [11][12][13][14][15][16][17][18]. It was demonstrated that the printable PSCs had passed the most popular international standards of IEC61215:2016 for mature PV technology [19].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4 b, the enlarged contact angle from 66° to 107° demonstrates the more hydrophobic surface of CsPbIBr 2 /NP‐GO. In addition, 2D graphene layer generally suppresses the diffusion of ions and therefore to enhance the environmental stability [5, 37, 38] . We have further aged the device under 150 °C for 16 hours to better understand the function of NP‐GO.…”
Section: Figurementioning
confidence: 99%
“…Moreover, although the use of a 2D network (such as graphene oxide, molybdenum disulfide, etc.) between perovskite and HTL is a considerable strategy for inhibiting ion migration from damaging the HTL, [ 28–32 ] it remains challenging to construct a robust and large‐area heterostructure without additional ionic dopants for efficient and stable PSC modules.…”
Section: Figurementioning
confidence: 99%